MANAGING LECTURER’S SERVICE QUALITY IN MEDAN AVIATION POLYTECHNIC BASED ON EFFECT OF TRAINING EFFECTIVITY AND JOB MOTIVATION - Syairi Anwar (Jurnal Maritim Malahayati, 2023)
The purpose of the study was to find out the level of lecturer’s service quality that is influenced by training effectivity and work motivation, so that ways and strategies can be formulated to improve the quality of education through improving lecturer’s service quality at Politeknik Penerbangan Medan. Statistical analysis method is done using Smart Partial Least Square (SmartPLS). Data collection was conducted through the dissemination of questionnaire instruments to the cadets with a sample of 214 people in total population of 528 people. From the results of this study obtained the value of path coefficient indirect training effectivity to lecturer’s service quality is 0.549. This means that the variable relationship of training effectivity to lecturer’s service quality through the intervening variable of work motivation value is positive and significant. This proves that the existence of intervening variable of work motivation value is full mediation or perfect because its presence results in a relationship between training effectivity to lecturer’s service quality that was previously negative and insignificant turned into positive and significant